2002
DOI: 10.1016/s0896-6273(02)01107-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Long-Term Synaptic Depression Requires PKC-Mediated Activation of CPI-17, a Myosin/Moesin Phosphatase Inhibitor

Abstract: Cerebellar LTD requires brief activation of PKC and is expressed as a functional downregulation of AMPA receptors. Modulation of vascular smooth-muscle contraction by G protein-coupled receptors (called Ca(2+) sensitization) also involves PKC phosphorylation and activation of a specific inhibitor of myosin/moesin phosphatase (MMP). This inhibitor, called CPI-17, is also expressed in brain. Here, we tested the hypothesis that LTD, like Ca(2+) sensitization, employs a PKC/CPI-17 cascade. Introduction of activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
54
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 61 publications
8
54
0
Order By: Relevance
“…Dephosphocytostatin (30 M), an inactive form of cytostatin, did not produce any marked effect on eEPSC amplitude (91 Ϯ 3%, n ϭ 4). In contrast, infusion of 100 nM fostriecin into immature PCs (12-15 DIV) did not depress eEPSCs (93 Ϯ 5%, n ϭ 8), confirming a recent report using young cerebellar cultures from mouse (15). All subsequent experiments were done on PCs aged 22-35 DIV (average 25.7 DIV).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Dephosphocytostatin (30 M), an inactive form of cytostatin, did not produce any marked effect on eEPSC amplitude (91 Ϯ 3%, n ϭ 4). In contrast, infusion of 100 nM fostriecin into immature PCs (12-15 DIV) did not depress eEPSCs (93 Ϯ 5%, n ϭ 8), confirming a recent report using young cerebellar cultures from mouse (15). All subsequent experiments were done on PCs aged 22-35 DIV (average 25.7 DIV).…”
Section: Resultssupporting
confidence: 85%
“…Although protein phosphatases (PPs) share with protein kinases the task of regulating protein phosphorylation level, they have long been considered mere housekeepers, with poorly understood substrate specificity and loose regulation. In recent years, however, studies using phosphatase inhibitors revealed that these enzymes exert a major influence on synaptic plasticity in the cerebellum (11)(12)(13)(14)(15) and other brain structures (16,17). In the cerebellum, investigation of AMPAR regulation by PP at the GC-PC synapse represents a challenge as PCs abundantly express at least five major types of serine͞threonine PPs: PP-1, PP-2A, PP-2B, PP-2C, and PP-5 (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…In this context, our result might be a missing puzzle fragment, that is, AMPA activated RhoA leading to polymeriz- ation of actin cytoskeleton and also phosphorylate moesin by RhoA-ROK leading to ligation of AMPA or NMDA receptor to underlying actin cytoskeleton since phopshorylation of moesin has been reported to be crucial in memebrane-cytoskeleton ligation (Bretscher et al, 2002). Recent study that a myosin/moesin phosphatase inhibitor, CPI-17 is crucial for cerebellar long-term depression through AMPA receptor (Eto et al, 2002) might be another clue for the role of moesin in AMPA receptor signaling. In this study, silencing CPI-17 by si-RNA blocked long-term depression (LTD) induction although significance of moesin phosphorylation in LTD is not directly proved.…”
Section: Am Pa Not Nm Da Phosphorylated M Oesin Through Rhoa-ro K Pmentioning
confidence: 70%
“…Thus, phosphorylation of CPI-17 suppresses myosin phosphatase activity, resulting in phosphorylation of myosin and contraction of smooth muscle. In addition, specific depletion of endogenous CPI-17 by small interfering RNA or antibody microinjection eliminated the cerebellar long-term synaptic depression of Purkinje cells mediated by PKC, demonstrating involvement of CPI-17 in neuronal signaling (21). Although phospho-CPI-17 inhibits monomeric PP1C in addition to myosin phosphatase, myosin phosphatase was proposed as a preferred target of phospho-CPI-17 in smooth muscle (22), fibroblasts (23), and cerebellar Purkinje cells (21).…”
mentioning
confidence: 99%